Water and Rights: Some Partial Perspectives - IIyer, Ramaswamy R. (Water Nepal, 2003)
Different users living or dependent on river make claim on the water. This claims can arise at the level of the household, farm, community, village or town, but occurs in more marked forms at the level of the political or administrative units within a country and at the level of ‘coriparian’ countries. Various principles and doctrines have been advanced in this regard. These have not yet been (and may fail to be) ratified by the required number of countries. This paper looks at these different instruments as partial perspectives. Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.153-163